2009
DOI: 10.25249/0375-7536.2009393560566
|View full text |Cite
|
Sign up to set email alerts
|

Biogeoquímica dos elementos terras raras na Província Estanífera de Pitinga (AM)

Abstract: Resumo A espécie vegetal Ampelozizyphus amazonicus Ducke (Família Rhamnaceae) foi escolhida como meio de amostragem nas superfícies lateríticas da Mina Pitnga, região amazônica, com o objetivo de se estudar o comportamento biogeoquímico dos elementos Terras Raras (ETR) nos solos derivados de rochas graníticas e vulcânicas ocorrentes na área da mina. Os resultados mostraram que a espécie A. amazonicus concentra valores significativos de ETR, predominantemente quando ocorrente nos solos derivados de rochas vulcâ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The REE concentration varied from 1 to 500 ppm depending on the plant species, organs and soil concentration. However, the internal processes of plants can fractionated the REE (Ding et al, 2006;Lima e Cunha et al, 2009). For example, Ding et al (2006) observed MREE enrichment in the roots and MREE and HREE enrichment in the leaves.…”
Section: Impact Of Biological Parametersmentioning
confidence: 99%
“…The REE concentration varied from 1 to 500 ppm depending on the plant species, organs and soil concentration. However, the internal processes of plants can fractionated the REE (Ding et al, 2006;Lima e Cunha et al, 2009). For example, Ding et al (2006) observed MREE enrichment in the roots and MREE and HREE enrichment in the leaves.…”
Section: Impact Of Biological Parametersmentioning
confidence: 99%